Sigorta aracılarının (acente, prodüktör, broker) Türk hukuk sistemi içerisindeki konumları ve birbirleriyle mukayesesi - Özdemir, Ayşe Zeynep Güç (My University, 2005)
Gelişmekte olan sigorta sektörü içinde, sigorta aracılarının sigorta sözleşmelerinin kurulmasına aracılık etme, sigorta yaptırmak isteyenlere danışmanlık yapma ve sözleşme süresince karşılaşılabilecek problemlerde taraflara yardımcı olma gibi mesuliyetlerinin olması, bu kişi ve kurumların sektördeki önemini arttırmaktadır. Türk Sigorta Hukuku'na göre, sigorta aracıları Sigorta acentesi, Sigorta prodüktörü, Sigorta brokeri olarak üçe ayrılmaktadır Sigorta acentesi, sigorta şirketini temsil ederken, sigorta prodüktörü kanun koyucuya göre tarafsız durumda, sigorta brokeri ise sigorta ettiren tarafında yer alır. Aracılar, kimin temsilcisi durumundaysalar o kişi ve kuruluşların hak ve menfaatlerini korumakla, direktiflerine uymakla yükümlüdürler. Bu tez çalışmasında her üç sigorta aracısının Türk Hukuk Sistemi içersindeki hukuki konumları, hak ve yükümlülükleri, sigorta şirketleri ve sigortalılarla olan ilişkileri incelenmiş, birtakım konularda birbirleriyle mukayeseleri yapılmıştır. Bütün bu incelemeler yapılırken, Yargıtay İçtihatlarına yer verilmiş, yurtdışı uygulamaları da göz önünde bulundurularak sigorta hukuku mevzuatımızda eksik olan taraflar ortaya konmak istenmiştir. Sigorta hukukumuzdaki, sigorta aracıları ile ilgili düzenlemeler bir çok açıdan eksik ve birbirleriyle çelişkili durumdadır. Sigorta acentelerinin niteliklerine, kuruluşlarına, faaliyetlerine, tesis edecekleri teminatlara, tutacakları defter,belge ve kayıt düzeni ile yapamayacakları işlere ve denetimlerine ilişkin düzenlemelerin yer aldığı Sigorta Acenteleri Yönetmeliği'nin Anayasa Mahkemesi'nce iptal edilmesi, buna rağmen yeni bir yönetmeliğin ihdas edilmemesi mevzuatımızda büyük boşluk yaratmaktadır. Ayrıca, sigorta brokerinin ve sigorta prodüktörünün hukuki mahiyetinin ne olduğu hususunda da doktrinde tartışmalar mevcuttur. Bu kavram kargaşası da mevzuatımızdaki düzenlemelerin yetersizliğinden ortaya çıkmaktadır. Sonuçta, öğretide ortaya çıkan tartışmalarla birlikte uygulamada karşılaşılan zorlukların giderilmesi amacıyla, hukukun ve sigorta sektörünün istikrarı açısından sigorta mevzuatımızda revizyona gidilmelidir. SUMMERY Recent decade has witnessed rapid developments in the insurance sector. In relation with this development, the importance and the responsibilities of the insurance mediators have increased tremendously since they are the ones in charge of assisting to the contracts as well as to any disputes arising from the contract. According to Turkish Law on Insurance, the insurance mediators are divided into three sub-groups which are: The Insurance Agent; The Insurance Producer; The Insurance Broker The insurance agent represents the insurance firm, whereas the insurance producer has to protect its distanced position in relation with the law making institutions. Lastly, the insurance broker has to be on the side of the customer with the insurance. The mediators are obliged to protect the rights and the interests of those people or the institutions which they represent. They further have to comply with the wishes of those represented. This dissertation examines the rights and the responsibilities of all three types of insurance mediators by counting on the regulations and statutes of the Turkish Law. Besides, the relations of those mediators with the insurance firms and the individual insurance customers are accounted for. In order to undertake this dissertation, besides the secondary literature, the rulings of the Supreme Court will be examined. Two interrelated reasons are sought for this emphasis on Supreme Court rulings. First is to understand the application of the law within the Turkish context. Second is to analyze the strengths and the weaknesses of the Turkish law on insurance so to be able to make a brief comparison with foreign applications. This dissertation shows the fact that the Turkish law on insurance does not cover all issues which concern with the workings and the relations of the insurance mediators. It is further asserted that some of the necessary regulations are either non-existent or they are in conflict with each other. One important reason for under-regulation within this fast growing sector is presented as the ruling of the Constitutional Court which invalidated The Regulations on the Insurance Agents This regulation was necessary since it defined the qualities of the insurance agents, the regulations for their establishments, their activities, the guarantees they could obtain, the records they could keep, and even the activities they could not get involved in.Moreover, although this regulation is invalidated, no replacement has taken place so far; a situation further increases the uncertanity and conflict within the sector. Last but not least, as it is clear from the continuing discussions, the doctrines that define the qualities of the insurance broker and the insurance producer are still not certain. It is suggested in this dissertation that all these uncertainities and inadequencies are stemming from the lack of well-defined regulations on the insurance mediators. In sum, the regulations on insurance should undergo a revision process in order to undo the amounting uncertainities and the conflicts that arise both in the doctrines and the applications of the Turkish law on insurance.
Keywords: Sigorta Hukuku_Türkiye